Valorising Agro-industrial Wastes within the Circular Bioeconomy Concept: the Case of Defatted Rice Bran with Emphasis on Bioconversion Strategies - Maria Alexandri; José Pablo López-Gómez; Agata Olszewska-Widdrat; Joachim Venus (Fermentation, 2020)
The numerous environmental problems caused by the extensive use of fossil resources have led to the formation of the circular bioeconomy concept. Renewable resources will constitute the cornerstone of this new, sustainable model, with biomass presenting a huge potential for the production of fuels and chemicals. In this context, waste and by-product streams from the food industry will be treated not as “wastes” but as resources. Rice production generates various by-product streams which currently are highly unexploited, leading to environmental problems especially in the countries that are the main producers. The main by-product streams include the straw, the husks, and the rice bran. Among these streams, rice bran finds applications in the food industry and cosmetics, mainly due to its high oil content. The high demand for rice bran oil generates huge amounts of defatted rice bran (DRB), the main by-product of the oil extraction process. The sustainable utilisation of this by-product has been a topic of research, either as a food additive or via its bioconversion into value-added products and chemicals. This review describes all the processes involved in the efficient bioconversion of DRB into biotechnological products. The detailed description of the production process, yields and productivities, as well as strains used for the production of bioethanol, lactic acid and biobutanol, among others, are discussed.